Oxidative stability of linseed oil nano-emulsions filled in calcium alginate hydrogels. (June 2020) - Rahiminezhad, Zahra; Hashemi Gahruie, Hadi; Esteghlal, Sara; Mesbahi, Gholam Reza; Golmakani, Mohammad-Taghi; Hosseini, Seyed Mohammad Hashem
Abstract: The main objective of this study was to fabricate calcium alginate hydrogels filled with linseed oil nanoemulsion (LON). Alginate beads were fabricated at different concentrations of sodium alginate (1% and 2%) and CaCl2 (0.25 and 0.5 M) and filled with whey protein isolate–stabilized LON. The hydrogels mechanical properties were influenced by the concentration of alginate and CaCl2 . An increase in the concentration of both constituents decreased the release of LON mainly due to increasing the compactness in the bead microstructure. The first derivative of FT-IR spectra revealed no chemical interaction between LON and alginate matrix. SEM micrographs revealed structural differences among various hydrogels. As determined by Raman spectral mapping, the higher alginate concentration led to more uniform distribution of LON. The amounts of lipid oxidation products developed in LON were decreased after its loading into the alginate beads. The GC-FID analysis of fatty acids profiles revealed that the alginate beads (particularly those prepared from the higher concentrations of alginate and CaCl2 ) could significantly (p < 0.05) retard the degradation of alpha-linolenic acid. The results of this study showed that the alginate beads are appropriate carriers for delivery of the emulsified form of functional lipids rich in polyunsaturated fatty acids. Highlights: Increasing concentration of alginate and CaCl2 improved bead mechanical properties. Oxidation of linseed oil (LO) was increased after formation of nanoemulsion (LON). Increasing concentration of alginate and CaCl2 reduced the LON release. Higher concentrations of alginate and CaCl2 enhanced the LON oxidative stability. Raman spectral mapping was used to determine the distribution of LON in hydrogels.